A Rare Phenotype of Uncommon Charcot–Marie–Tooth Genotypes Complicated With Inflammation Evaluated by Genetics and Magnetic Resonance Neurography - Su, Xiaoyun; Kong, Xiangquan; Lu, Zuneng; Wang, Lixia; Zheng, Chuansheng (Frontiers in Genetics, 2022)
The pathogenesis of Charcot–Marie–Tooth (CMT) disease, an inherited peripheral neuropathy, is associated with more than 60 nuclear genes. We reported a rare phenotype of the uncommon CMT genotype complicated with neuroinflammation, that is, an MPZ mutation, NC_000001.11 (NM_000530.6): c.308G > C detected by next-generation sequencing. Moreover, we present a case of the CMT type 1B, with atypical presentation as two patterns of hypertrophy in the brachial and lumbosacral plexus, as well as enhancement in the cauda equina and nerve roots on multimodal magnetic resonance neurography (MRN). MRN assessment facilitated the identification of coexisting neuroinflammation and provided more evidence, especially for patients with atypical symptoms in hereditary sensory and motor neuropathy, who could benefit from immunotherapy.